Keterampilan Guru dalam Pengelolaan Kelas untuk Meningkatkan Keaktifan Belajar Siswa - Melkior Ecan (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Kupang, 2025)
This study aims to describe teachers’ classroom management skills in enhancing students’ learning activeness in Grade XI at SMA Negeri 6 Kupang. This research employs a descriptive qualitative approach with research subjects consisting of the school principal, four teachers, and six students. Data collection techniques include observation, interviews, and documentation, while data analysis involves data reduction, data display, and conclusion drawing. The findings reveal that teachers’ classroom management skills that significantly improve students' learning activeness include designing classroom layout, establishing a positive learning climate, managing time effectively, regulating student behavior, utilizing learning media and technology, and developing supportive interpersonal relationships. Supporting factors include adequate learning facilities, school administrative support, and literacy and extracurricular programs. Meanwhile, inhibiting factors include diverse learning styles, large class sizes, varied student backgrounds, limited instructional time, and lack of parental involvement. The study underscores classroom management as a pedagogical competency requiring synergistic support from teachers, schools, students, and families.